Assessment of Lower Limb Joint Postural Deformities Using APECS among Male Physical Education and Sport Science Applicants - Abbas , Haider; Shehab , Rusul; Atiyah , Hasan; Shehab , Raghda (Journal of Physical Education, 2025)
The Alignment Posture Evaluation and Correction System (APECS) is a non-radiographic AI-based mobile application designed to assess body posture safely and accurately, unlike X-rays, which may be harmful and less precise. This study used APECS version 2.0 (DXM model) to detect lower limb deformities in hip, knee, and foot joints among 60 male applicants to the College of Physical Education and Sports Science. Full-limb images with anatomical markers were captured, and joint angles were automatically calculated by the software. Results indicated deformities in the hip (18.35%), knee (26.61%), and foot (41.28%). The program demonstrated high accuracy, with a 98.74% matching rate and 94.64% agreement, confirming its validity as a reliable, non-invasive tool for assessing lower limb postural deformities in prospective students.